2013
DOI: 10.1177/0010414013495361
|View full text |Cite
|
Sign up to set email alerts
|

Partisan Politics and Privatization in OECD Countries

Abstract: Many scholars have argued that partisan differences have disappeared since the 1980s because of the ever-increasing economic globalization and the deepening of European integration. Using a new primary data set on public ownership that contains detailed information on privatization in 20 countries between 1980 and 2007, we test these claims empirically in relation to state ownership. We pay special attention to the question of whether changes in the international political economy, notably globalization and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
2
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 38 publications
1
44
2
2
Order By: Relevance
“…Therefore, policies that might break up these corporatist networks and undermine the power of interest groups and established parties can be expected to find PRRP support. Trade unions, in particular, are among the most purposeful defenders of regulation (Davidsson and Emmenegger, 2013) because both labour market deregulation and privatization of formerly state-owned enterprises directly concern their own power base (Obinger et al, 2014). Hence, the deregulation of these domains should be in the direct interest of both PRRPs as well as pro-business mainstream right parties.…”
Section: Office-seeking Strategiesmentioning
confidence: 99%
“…Therefore, policies that might break up these corporatist networks and undermine the power of interest groups and established parties can be expected to find PRRP support. Trade unions, in particular, are among the most purposeful defenders of regulation (Davidsson and Emmenegger, 2013) because both labour market deregulation and privatization of formerly state-owned enterprises directly concern their own power base (Obinger et al, 2014). Hence, the deregulation of these domains should be in the direct interest of both PRRPs as well as pro-business mainstream right parties.…”
Section: Office-seeking Strategiesmentioning
confidence: 99%
“…This study therefore aligns with other literature that have rejected the "end of partisanship" theory and demonstrated the continued existence of a substantial partisan effect even during an era of welfare state retrenchment (Allan and Scruggs 2004;Amable, Gatti, and Schumacher 2006;Belke et al 2007;Boix 1997;Bortolotti et al 2003;Obinger et al 2014;Palme and Korpi 2003;Zehavi 2012).…”
supporting
confidence: 89%
“…To provide a few examples, Bortolotti et al (2003) presented evidence that the right-wing parties were more likely to privatise, whereas Belke et al (2007) determined that there were partisan differences in opinions of privatisation in 22 advanced democracies in the 1990s. Obinger et al (2014) summarised that political parties have continued to significantly shape national privatisation trajectories in line with the classical hypothesis of partisan distinction. Furthermore, Gerber and Lewis (2004) concluded that legislators regularly take positions that diverge significantly from the preferences of the median voter in their districts.…”
Section: Introductionmentioning
confidence: 80%
“…Different outcomes in economic policy‐making can be reliably linked to government ideology in the OECD (Boix, ; Korpi and Palme, ): Left‐wing governments tend to enact more protective labor market regulation (Botero et al 2004) and spend more on work training (Iversen and Stephens, ). By contrast, right‐wing governments are relatively more supportive of deregulating product markets (Potrafke, ) and privatization (Bortolotti and Pinotti, ; Obinger et al, ).…”
Section: Does Government Ideology Still Matter?mentioning
confidence: 99%
“…In the OECD, the empirical evidence is mixed. Some studies show that the partisan effect disappears for some areas, particularly for welfare spending (Garrett and Mitchell, ; Huber and Stephens, ; Kittel and Obinger, ; Potrafke, ; Kwon and Pontusson, ; Herwartz and Theilen, ), while it remains significant for market regulation and privatization (Bortolotti and Pinotti, ; Iversen and Stephens, ; Potrafke, ; Obinger et al, ).…”
Section: Introductionmentioning
confidence: 99%